2013
DOI: 10.1108/lr-10-2012-0113
|View full text |Cite
|
Sign up to set email alerts
|

Brain drain in African academic libraries: a survey

Abstract: PurposeThis study was intended to identify and assess the extent and impact of the emigration of professional librarians on every university library in Anglophone Africa as well as the attitudes of library administrators toward national and international programs that have been or might be designed to make use of the skills of librarians in the African diaspora.Design/methodology/approachThe research was conducted by use of an online survey that was sent to 121 African academic libraries.FindingsThe study conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This represented a 55.3 per cent response rate. Although this were the case, the response rate was still good when compared with other studies (Ibraheem and Devine, 2013;Treptow and James, 2011;Fullard, 2007). These studies have shown that use of emails, as a data collection method normally elicits a poor response rate.…”
Section: Response Ratementioning
confidence: 67%
See 2 more Smart Citations
“…This represented a 55.3 per cent response rate. Although this were the case, the response rate was still good when compared with other studies (Ibraheem and Devine, 2013;Treptow and James, 2011;Fullard, 2007). These studies have shown that use of emails, as a data collection method normally elicits a poor response rate.…”
Section: Response Ratementioning
confidence: 67%
“…These studies have shown that use of emails, as a data collection method normally elicits a poor response rate. The study conducted by Fullard (2007) achieved a 29.0 per cent response rate, while studies conducted by Ibraheem and Devine (2013) and Treptow and James (2011) achieved even lower response rates of 19.8 per cent and 14.0 per cent respectively. Although 47 questionnaires administered to the LIS graduates were returned, the researcher observed that some of the respondents did not respond to some questions.…”
Section: Response Ratementioning
confidence: 87%
See 1 more Smart Citation